2002
DOI: 10.1097/00006842-200205000-00010
|View full text |Cite
|
Sign up to set email alerts
|

An Exercise Program for Women Who Are Caring for Relatives With Dementia

Abstract: This study demonstrates the feasibility and success of delivering home-based health promotion counseling for improving physical activity levels in a highly stressed and burdened population. Given the independent risk factors of caregiving and physical inactivity on mortality, programs to improve healthful behaviors are needed to preserve the health of caregivers as they undertake this important familial and societal role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 40 publications
3
81
2
2
Order By: Relevance
“…First, it seems non-frequent contact strategies might be as effective as frequent contact strategies in raising physical activity or physical capacity. This is not in line with literature stating that a higher contact frequency is directly related to higher adherence [41,43] or effectiveness. However, it must be mentioned that especially in the frequent contact group the heterogeneity in studies was large.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…First, it seems non-frequent contact strategies might be as effective as frequent contact strategies in raising physical activity or physical capacity. This is not in line with literature stating that a higher contact frequency is directly related to higher adherence [41,43] or effectiveness. However, it must be mentioned that especially in the frequent contact group the heterogeneity in studies was large.…”
Section: Discussioncontrasting
confidence: 87%
“…Social-cognitive strategies to enhance self-efficacy were used in two studies [29,31,36]. Eleven other studies mentioned using individualized feedback, education or encouragement [10,21,22,24,26,27,29,30,34,37,43]. The studies using a direct remote contact strategy did not report using specific theory-based motivational or coaching strategies [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,16,17 We identified three major health promotion barriers: heavy caregiving and non-caregiving roles and responsibilities; CG concerns regarding their mental and physical health, and absence of support from others; and environmental concerns, which are similar to those commonly noted by others. 11,14,17 Given the number of barriers identified, more individualized attention and strategies for overcoming barriers need to be considered. The interventionist addressed barriers during each telephone session using information-sharing, problem-solving and supportive methods.…”
Section: Discussionmentioning
confidence: 96%
“…After that, there is a stabilization with small declines 36 in the neurodegenerative characteristics of the disease. Taking that into consideration, participation in the intervention program seems to contribute to reduction in the progressive impairment of cognition and behavior and could alleviate patient suffering, thus helping caregivers manage their patients as shown in another study 37 . The results are consistent with studies that showed clinical relevance in the positive effects of the practice of exercise combined with pharmacological treatment in AD patients as shown by a meta-analysis 38 .…”
Section: Discussionmentioning
confidence: 93%